Modification of Polypeptide-graft-poly(ethylene glycol) Film by Blending with Poly(butyl acrylate-co-methyl methacrylate) - Zhu, Guo-Quan; Wang, Fa-Gang; Xu, Ke-Jing; Gao, Qiao-Chun; Liu, Yu-Ying (Asian Journal of Chemistry, 2013)
A series of poly(g-benzyl L-glutamate)-graft-poly(ethylene glycol)/poly(butyl acrylate-co-methyl methacrylate) (PBLG-graft-PEG/P(BA-co-MMA)) blend films were prepared by the solution casting method. Surface morphologies of the polymer blend films were investigated by scanning electron microscopy. Mechanical and chemical properties of the polymer blend films were studied using tensile tests and contact angle tests. It was revealed that the introduction of P(BA-co-MMA) into polypeptide graft copolymer could exert marked effects on the surface morphology and the properties of the polypeptide graft copolymer film.